Respostas

2014-05-04T16:12:39-03:00


por fim achamos a raíz de dentro do parentese 

-x + 6 = 0 
-x = -6 
x = 6
2014-05-04T16:43:21-03:00
 6x=0  
X
=6/0 x=6                                                                                                                                                    x-64=0
                              x=64/0
                                x=64                                                                                                                                                  2x-32=0
                                                    x=32/2 x=16
9x=0
x=9/0 x =9

(x-2).(x-1)=0
X² -x=2x-2
X²-3x+2=0
Δ=-3²-4.1.2
Δ=9-8=1
X=3(+ -)1/2
X'=4
X"=1